Evangelical Christianity and the Family - Stanko Jambrek (Kairos (English Ed.), 2009)
Evangelical Christians in Croatia and elsewhere in the world attempt to apply the principles of the Holy Scriptures in their daily lives, and their marriages and family lives are probably the most significant and most evident indicators of the success of that application. The first part of this article deals with the basics of biblical teaching on marriage and the family. In the second part, the stance of evangelical Christians is outlined on topics such as sexual immorality, especially regarding sexual intercourse before marriage and outside of marriage, as well as their attitude on homosexuality. In the last part of the article, the author offers biblical/theological guidelines for raising children and strengthening the family that include the establishment of living on the foundation of God’s Word, the establishment of biblical authority in the marriage and family, as well as the establishment of family priorities.